RNA-binding protein immunoprecipitation as a tool to investigate plant miRNA processing interference by regulatory proteins of diverse origin - Marmisollé, Facundo Ernesto (2018)
Background: Due to the nature of viral RNA genomes, RNA viruses depend on many RNA-binding proteins (RBP) of viral and host origin for replication, dissemination and evasion of host RNA degradation pathways. Some viruses interfere with the microRNA (miRNA) pathway to generate better fitness. The development of an adjusted, reliable and sensitive ribonucleoprotein immunoprecipitation (RIP) assay is needed to study the interaction between RBP of different origin (including viral origin) and miRNA precursors. The method could be further applied to transiently expressed heterologous proteins in different plant species. Results: Here we describe a modified RIP assay applied to nuclear epitope-tagged proteins of heterologous origin and transiently expressed in Nicotiana benthamiana. The assay includes a combination of optimized steps as well as the careful selection of control samples and rigorous data analysis. It has proven efficient to detect and quantify miRNA processing intermediates associated with regulatory proteins. Conclusions: The RIP method described here provides a reliable tool to study the interaction of RBPs, such as transiently expressed regulatory proteins with lowly represented host RNA, as is the case of miRNA precursors. This modified method was efficiently adjusted to recover nuclear proteins and reduce unspecific background. The purification scheme optimized here for GFP-tagged proteins can be applied to a wide array of RBPs. The subsequent application of next-generation sequencing technologies will permit to sequence and characterize all RNA species bound in vivo by a given RBP.